PENGARUH KOMPRES HANGAT TERHADAP PENURUNAN NYERI LEHER PADA PENDERITA HIPERTENSI DI RSUD ARIFIN ACHMAD PROVINSI RIAU - Marlina Desi; Dyah Wulan Ramadhani; Anita Syarifah (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Hypertension is a condition when the blood pressure against the artery wall is too high, where the systolic blood pressure exceeds 140 mmHg, and the systolic blood pressure is less than 90 mmHg. There are many therapies available to relieve pain in patients with hypertension. One of them is a warm compress that aims to stimulate the skin surface to relieve pain. The purpose of this study was to determine the effect of warm compresses on reducing neck pain in patients with hypertension. The research design used is quantitative research with quasi-experimental methods with a two group pre test and post test design. This research was conducted on January 06-18, 2025. The population in this study were hypertensive patients at Arifin Achmad Hospital, Riau Province, as many as 217 people and a sample of 60 people divided into 2 groups of 30 people with warm compress intervention and 30 control people without any treatment. The sampling technique used purposive sampling. Data collection tools using observation sheets and self-report. Analysis for the intervention group using the wilxocon test with a P-Value of 0.000 (0.05) means that there is an effect of warm compresses on reducing neck pain in hypertension. While analyzing for the control group using the Wilcoxon test with a P-Value of 0.008 (0.005), it means that there is no effect of warm compresses on reducing neck pain in hypertension.Keywords: Hypertension, Pain, Warm Water Compress